Fabrication of SnO2 Nanopaticles/BiOI n–p Heterostructure for Wider Spectrum Visible-Light Photocatalytic Degradation of Antibiotic Oxytetracycline Hydrochloride - Wen, Xiao-Ju; Niu, Cheng-Gang; Zhang, Lei; Zeng, Guang-Ming (ACS sustainable chemistry & engineering, 2017)
In this work, n–p heterostructure SnO2/BiOI photocatalyst was successfully fabricated through a facile chemical bath method. The photocatalysts was applied to minimize antibiotic oxytetracycline hydrochloride (OTTCH) and methyl orange (MO) under visible light irradiation. SnO2/BiOI composite exhibited excellent photocatalytic performance for the refractory pollutant OTTCH and MO decomposition. The sample of 30 wt % SnO2/BiOI possessed the best photocatalytic performance in all the obtained catalysts. Several reaction parameters affecting OTTCH degradation such as initial concentration, ion species, and concentration were investigated systematically. The optical and electrical properties of materials demonstrate that the transfer rate of electron–hole pairs dramatically improve though forming an n–p junction in SnO2/BiOI hybrid. Moreover, the energy band alignments of SnO2/BiOI junction were confirmed via combining DRS and XPS analysis, which provided strong support for the proposed mechanism. This work could provide a new approach to construct new p–n junction photocatalysts and a reference for the study of other heterojunction catalysts.